Formal mentorship in a surgical residency training program: a prospective interventional study. Issue 1 (December 2017) - Zhang, Han; Isaac, Andre; Wright, Erin; Alrajhi, Yaser; Seikaly, Hadi
Abstract Background Otolaryngology-Head and Neck surgery resident physicians (OHNSR) have a high prevalence of burnout, job dissatisfaction and stress as shown within the literature. Formal mentorship programs (FMP) have a proven track record of enhancing professional development and academic success. More importantly FMP have an overall positive impact on residents and assist in improving job satisfaction. The purpose of the study is to determine the effects of a FMP on the well-being of OHNSR. Methods A FMP was established and all OHNSR participation was voluntary. Eight OHNSR participated in the program. Perceived Stress Survey (PSS) and the Maslach Burnout Inventory (MBI) were administered at baseline and then at 3, 6, 9, and 12 month intervals. World Health Quality of Life-Bref Questionnaire (WH-QOL) was administered at baseline and at 12 months. Results Baseline statistics found a significant burden of stress and burnout with an average PSS of 18.5 with a high MBI of 47.6, 50.6, and 16.5 for the emotional, depersonalization, and personal achievement domains respectively. Quality of life was also found to be low with a WH-QOL score of 71.9. After implementation of the FMP, PSS was reduced to 14.5 at 3 months (p = 0.174) and a statistically significant lower value of 7.9 at 12 months (p = 0.001). Participants were also found to have lower emotional scores (14.9, p < 0.0001), levels of depersonalization (20.1, p < 0.0001), and higher personal achievement (42.5, p < 0.0001) on MBI testing at 12 months. Overall quality values using the WH-QOL was also found to be significantly improved (37.5, P = 0.003) with statistically significant lower scores for the physical health (33.9, p = 0.003), psychological (41.1, p = 0.001), social relationship (46.9, p = 0.019), and environment (53.5, p = 0.012) domains. Conclusion This is the first study to show that FMP can potentially alleviate high levels of stress and burnout within a surgical residency program and achieve higher levels of personal satisfaction as well as overall quality of life.